2017
DOI: 10.1002/2016ms000787
|View full text |Cite
|
Sign up to set email alerts
|

Decadal climate predictions improved by ocean ensemble dispersion filtering

Abstract: Decadal predictions by Earth system models aim to capture the state and phase of the climate several years in advance. Atmosphere‐ocean interaction plays an important role for such climate forecasts. While short‐term weather forecasts represent an initial value problem and long‐term climate projections represent a boundary condition problem, the decadal climate prediction falls in‐between these two time scales. In recent years, more precise initialization techniques of coupled Earth system models and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 58 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…The ensemble resampling approach in EDF is close to that of jackknife resampling (Quenouille, ). The EDF was shown to lead to more accurate predictions than those from the MiKlip prediction system in terms of global mean and regional temperature, precipitation, and winter cyclones (Kadow et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The ensemble resampling approach in EDF is close to that of jackknife resampling (Quenouille, ). The EDF was shown to lead to more accurate predictions than those from the MiKlip prediction system in terms of global mean and regional temperature, precipitation, and winter cyclones (Kadow et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, initialization using full-field observational values can lead to initial shocks affecting skill (Kröger et al 2018) and in such cases initialization combining observed anomalies with the model's own climatology can be beneficial until underlying model errors can be reduced (Volpi et al 2017). Basic initialization strategies continue to be an active research area particularly for decadal prediction (Brune et al 2018), and methods extending to forecast runs such as the ensemble dispersion filter, which replaces the ensemble members with the ensemble mean every 3 months (Kadow et al 2017) are also being explored. Comparisons that apply different initialization methods to the same model can yield valuable insights (Polkova et al 2019); further issues specific to the initialization of the land, ocean, and sea ice components are considered in the next section.…”
Section: E879mentioning
confidence: 99%
“…In general, the IE does not greatly change the mean state of SST, but slight shifts are found, for example, in the Gulf Stream/North Atlantic current region ( Figure S5). There are large regions like the subtropical North Atlantic showing relatively longer predictability with the IE, which could be simply explained by the noise reduction in the IE suggesting that the noise is an important factor limiting predictability (Kadow et al, 2017). Nevertheless, there are considerable regions showing shorter decadal predictability such as the subpolar North Atlantic.…”
Section: Decadal Sst Predictabilitymentioning
confidence: 99%